Organisational Attributes and Corporate Monitoring Mechanisms - Mazlina, Mustapha (2009)
Monitoring mechanisms that are mandatory for Malaysian public listed companies are internal auditing, external auditing and directorship. There is a comparative advantage of each type of these mechanisms and they complement each other. It is said that the attributes of an organisation can influence its monitoring costs, as the costs are the function of the systems adopted by the organisation. This is important as the costs involve may jeopardise the shareholders wealth and future survival of the organisation. Thus, this thesis investigates the impacts of these organisational attributes on the demands and preferences of these three monitoring mechanisms among Malaysian public listed companies. The organisational attributes that are examined are ownership structure, debt structure, information system structure, compensation structure, multinational status and ethnicity. The results of this study provide evidence that are consistent to agency theory; managerial shareholdings and debt structure appear to have negative significant relationships with monitoring costs. However, another ownership variable seems to give different finding compared to those studies in western countries.Block-holders appear to demand more monitoring costs, which may be due to the concentrated business environment in Malaysia. Other organisational attributes which are significant in its association with monitoring costs are multinational status and ethnicity. Investigation on the preference between directorship and auditing with these organisational attributes reveal that managerial ownership, compensation structure and ethnicity are significant. Further examinations on the impact of these attributes on the preference between internal and external auditing indicate that, debt structure,information system structure, multinational status and ethnicity are significant.